OBTAINING CATALYSTS FOR ISOMERIZATION PROCESSES OF LIGHT PETROL FRACTIONS - Karshiyev, Murodulla (Innovatsion texnologiyalar, 2024)
Today, the production of gasoline that meets Euro-5 and Euro-6 requirements is considered relevant. In this work, to increase the isomerization ability of the catalysts, the catalyst support, aluminum oxide, was treated with hydrogen chloride. The main purpose of this is to increase the acidity level of the alumina, and the acidity level of the catalysts is directly related to its isomerization ability, that is, the higher the acidity level of the catalyst, the higher its isomerization ability. The results obtained show that the catalysts have similar properties. This can be explained by the fact that the basis of these catalysts is aluminum oxide, and the concentrations of hardened metals are almost close to each other. It should be noted here that the sorption performance of these catalysts is close to that of isomerization catalysts used in industry. The antifriction strength of the resulting catalysts was determined according to GOST 16188-2015. This standard is intended to determine the resistance of catalysts and sorbents to mechanical friction. This method is based on rotating a catalyst sample in an iron drum with a metal rod rotating at a certain constant speed. It was observed that the strength of the catalyst remained unchanged after cycling for a certain period of time.